Descriptive Analysis of Learning Strategies in Motivating Students in the Qur'an Tahfiz Program - Ika Pratiwi Addas; Mardi Takwim; Haris Kulle (State Islamic Institute of Palopo, 2022)
This thesis discusses the descriptive analysis of strategies to motivate students in the tahfiáº“ al-Qur'an program at the Muhammadiyah Boarding School (MBS) Islamic Boarding School in Palopo City. The objectives of this study were: to describe the motivation of students, to analyze the learning strategy of tahfiáº“ al-Quran, and to describe the factors supporting and inhibiting the application of the learning strategy of the tahfiáº“ al-Qur'an program at the Palopo MBS Islamic Boarding School. This research uses descriptive qualitative research with data collection techniques namely observation, interviews, and documentation. Respondents in this study were directors, teachers, and students. The researcher used the triangulation technique. The results showed that the motivation of students in the tahfiáº“ al-Qur'an Islamic boarding school program by looking at the amount of memorization of all students in class IX after going through many challenges, was still increasing and this was considered to be running smoothly because there were several motivating students in learning, namely: 1) The existence of a conducive learning environment; 2) Tenacious in the face of adversity; 3) The existence of future aspirations such as wanting to become a prayer priest, giving a crown of glory to his parents, becoming an Ustaz and hafiáº“ of the Qur'an and scholarships; 4) There is appreciation in learning; 5) There is encouragement and need in learning; 6) Interesting activities. Learning strategies in motivating students in the tahfiáº“ al-Qur'an Islamic boarding school program have been running optimally, because several strategies are applied and are considered capable of making students motivated, namely: 1) Explaining the virtues of memorizing the Qur'an; 2) Giving muroja'ah assignments; 3), Provide rote targets; 4) Giving Value; 5) Giving Gifts, 6) Giving Punishments, 7) Santri are scheduled to be priests of prayer, 8) Telling about the experience of Ustadz; 9) Opening a special program for tahfiáº“ al-Qur'an. Some support the tahfiáº“ al-Qur'an program, namely the teacher of a hafiz al-Qur'an, the wishes of students and encouragement from parents, and solid cooperation between students and teachers. While the inhibiting factors for teachers in the tahfiáº“ al-Qur'an program are the effects of the COVID-19 pandemic and some students have an unstable memorization spirit. The research implication is that the motivation of students in the tahfiáº“ program will increase if the students are facilitated by the memorization target book as a guide, so that they are more motivated to add new memorization and try to maintain the old memorization if they are prepared not only in tahfiáº“ al-Qur'an competitions between Muhammadiyah Islamic boarding schools, but also in the Musabaqoh Tilawatil Qur'an (MTQ) activity.